2020
DOI: 10.1155/2020/8810785
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanisms of Regulating Oxidative Stress-Induced Ferroptosis and Therapeutic Strategy in Tumors

Abstract: Ferroptosis is an atypical form of regulated cell death, which is different from apoptosis, necrosis, pyroptosis, and autophagy. Ferroptosis is characterized by iron-dependent oxidative destruction of cellular membranes following the antioxidant system’s failure. The sensitivity of ferroptosis is tightly regulated by a series of biological processes, the metabolism of iron, amino acids, and polyunsaturated fatty acids, and the interaction of glutathione (GSH), NADPH, coenzyme Q10 (CoQ10), and phospholipids. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 118 publications
0
63
0
Order By: Relevance
“…Ferroptosis, a necrosis-like type of programmed cell deaths ( 159 ), is attracting attention as a key mechanism involved in the development of future cancer therapies ( 160 , 161 , 162 , 163 ). In ferroptotic cells, the accumulation of lipid peroxides and lipid hydroxyl radicals generated by iron leads to cell death ( 159 , 164 ).…”
Section: New Challenges For Understanding Bach1 At Crossroads Of Cancer Biologymentioning
confidence: 99%
“…Ferroptosis, a necrosis-like type of programmed cell deaths ( 159 ), is attracting attention as a key mechanism involved in the development of future cancer therapies ( 160 , 161 , 162 , 163 ). In ferroptotic cells, the accumulation of lipid peroxides and lipid hydroxyl radicals generated by iron leads to cell death ( 159 , 164 ).…”
Section: New Challenges For Understanding Bach1 At Crossroads Of Cancer Biologymentioning
confidence: 99%
“…Further studies have shown that FSP1 reduces coenzyme Q10 via NADPH to inhibit ferroptosis ( Zhu et al, 2020 ). The NADPH/FSP1/CoQ10 system is therefore a negative regulator of ferroptosis.…”
Section: Signaling Pathways Of Ferroptosis Associated With Atherosclerosismentioning
confidence: 99%
“…Abnormally elevated levels of oxidative stress (ROS) are widely accepted as one of the hallmarks of cancer [ 72 ]. ROS is usually regarded as a toxic substance in cells, and when high ROS cannot be metabolized properly, cells will die or become cancerous.…”
Section: The Association Between Ho-1 and Abnormal Oxidative Stress In Cancer Diseasesmentioning
confidence: 99%